2017
DOI: 10.1186/s13068-017-0752-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative insights into the saccharification potentials of a relatively unexplored but robust Penicillium funiculosum glycoside hydrolase 7 cellobiohydrolase

Abstract: BackgroundGH7 cellobiohydrolases (CBH1) are vital for the breakdown of cellulose. We had previously observed the enzyme as the most dominant protein in the active cellulose-hydrolyzing secretome of the hypercellulolytic ascomycete—Penicillium funiculosum (NCIM1228). To understand its contributions to cellulosic biomass saccharification in comparison with GH7 cellobiohydrolase from the industrial workhorse—Trichoderma reesei, we natively purified and functionally characterized the only GH7 cellobiohydrolase ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Here, we simply note that the investigated system shows a strong correlation between low affinity and poor thermoactivation, and hence that there appears to be a causal relationship. Several earlier studies of temperature effects on cellulases acting on real cellulose have also shown weak thermoactivation (Ogunmolu et al, ; Sorensen et al, ; Voutilainen et al, ; Ye & Berson, ; Zhang et al, ), and one particularly clear example of this was recently described by Teugjas and Valjamae (). They found that the activity of a cellulase mixture (dominated by Cel7A) decreased when the experimental temperature was raised from 40 °C to 55 °C.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Here, we simply note that the investigated system shows a strong correlation between low affinity and poor thermoactivation, and hence that there appears to be a causal relationship. Several earlier studies of temperature effects on cellulases acting on real cellulose have also shown weak thermoactivation (Ogunmolu et al, ; Sorensen et al, ; Voutilainen et al, ; Ye & Berson, ; Zhang et al, ), and one particularly clear example of this was recently described by Teugjas and Valjamae (). They found that the activity of a cellulase mixture (dominated by Cel7A) decreased when the experimental temperature was raised from 40 °C to 55 °C.…”
Section: Discussionmentioning
confidence: 87%
“…This is challenging because saccharification relies on a cocktail of synergizing enzymes, which must all be stable, but there has been good progress in this field, and a number of thermostable cellulases have been described (Heinzelman et al, ; Voutilainen, Murray, Tuohy, & Koivula, ). However, the degree of thermoactivation on real cellulose for these thermostable enzymes has generally been moderate (Ogunmolu et al, ; Sorensen et al, ; Voutilainen et al, ; Ye & Berson, ; Zhang et al, ) compared to typical bulk enzyme‐substrate systems (Elias et al, ), including cellulases acting on soluble substrate‐analogs (German, Marcelo, Stone, & Allison, ). In the current work, we suggest that this comparably lower thermoactivation on real cellulose reflects a temperature induced desorption of cellulases from the substrate surface, and show that engineering of a “high‐affinity” variant mitigated this problem and hence improved thermoactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier investigations of Cel7A's pH profile have mostly used soluble substrate analogs (see Section ), and like the current work on pNPL (Figure ) they have all found the characteristic slope of the acidic limb of the profile. Some earlier studies have reported pH profiles for fungal Cel7As based on activity measurements on Avicel (Colussi et al, ; Marjamaa et al, ; Ogunmolu et al, ). Unlike the results in Figure , however, these reports found sloping acidic limbs although the slope was quite shallow except in one case (Ogunmolu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies have reported pH profiles for fungal Cel7As based on activity measurements on Avicel (Colussi et al, ; Marjamaa et al, ; Ogunmolu et al, ). Unlike the results in Figure , however, these reports found sloping acidic limbs although the slope was quite shallow except in one case (Ogunmolu et al, ). These previous profiles on Avicel were all made at low substrate loads (5–10 g/L), and to test possible effects of this, we repeated the measurements at 40°C with very low load (1 g/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation